2013
DOI: 10.1007/s00784-013-0972-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological indicators of dental caries and periodontal disease in adolescents with or without obesity

Abstract: Customised oral health preventive programmes and appropriate collaboration with medical personnel in selecting the best diet, medication and psychological support can help improve the general well-being, including oral health, of children with obesity. This may even reduce the risk of oral diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 42 publications
1
79
2
4
Order By: Relevance
“…Obese children and adolescents had the higher PPD, PI, GI, and BOP values than normal weight counterparts . It has been speculated that unhealthy dietary habits and poor oral hygiene attitude in obese children may lead to the higher plaque scores which is associated with the higher GI and BOP . In contrast to aforementioned studies, our data revealed that obese children had similar PPD, PI, and GI values to normal weight children although they had higher BMI values as expected.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Obese children and adolescents had the higher PPD, PI, GI, and BOP values than normal weight counterparts . It has been speculated that unhealthy dietary habits and poor oral hygiene attitude in obese children may lead to the higher plaque scores which is associated with the higher GI and BOP . In contrast to aforementioned studies, our data revealed that obese children had similar PPD, PI, and GI values to normal weight children although they had higher BMI values as expected.…”
Section: Discussioncontrasting
confidence: 62%
“…BMI, the reliable indicator of body fat mass, was found to be positively associated with the gingival bleeding accepted as a stronger indicator of gingival inflammation. Obese children and adolescents had the higher PPD, PI, GI, and BOP values than normal weight counterparts . It has been speculated that unhealthy dietary habits and poor oral hygiene attitude in obese children may lead to the higher plaque scores which is associated with the higher GI and BOP .…”
Section: Discussionmentioning
confidence: 99%
“…The few available studies in this topic assessed the lipid profile using BMI, and presented very contrasting results, e.g. significant association between obesity and gingivitis . Meanwhile, another study found such association only in males and no impact of obesity in gingival inflammation is also reported in the literature …”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a highly prevalent condition characterized by the abnormal accumulation and storage of fat in adipose tissue (Boesing, Patiño, da Silva, & Moreira, ) and produced by an imbalance between energy intake and energy expenditure, which can be modified by genetic and environmental circumstances (Fadel et al., ). Obesity is associated with chronic, low‐grade inflammation, which is involved, in turn, in the development of insulin resistance (IR) (Bullon et al., ), and is a major contributor to the development of hypertension, type 2 diabetes mellitus, arteriosclerosis, cardiovascular and cerebrovascular diseases (Haffajee & Socransky, ; Pischon et al., ; Saito & Shimazaki, ).…”
Section: Introductionmentioning
confidence: 99%